I'jaz Al-Quran in Linguistic Perspective and it’s Impact on The Readers - Thonthowi, Thonthowi; Mukhlis, Abdul; Annafiri, Ahmad Zaki; Sarif, M. Iqbal; Muslim, M. Damar (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
As a miracle given to the Prophet Muhammad SAW, Al Quran has miraculous aspects from various aspects, including editorial balance, scientific information, information of the past and future, as well as the beauty of the style of expression in terms of language. This miracle establishes that Al Quran is not only special in terms of its content, but also in terms of the letters, words, sentences, letters and section that make it up. The objectives of this research are: 1) Describe the definition, elements and meaning of I'jaz Al-Quran, 2) Describe the miracles and beauty of the style of expressing the Al-Quran from a linguistic perspective, 3) Describe the impact of I'jaz Al-Quran on readers. The results of this research: 1) Miracles in Al Quran are miracles that are owned or contained in Al Quran, rather than evidence of truth that comes from outside Al Quran or external factors, then the elements accompanying the miracle must be 'extraordinary', shown by a prophet , contains challenges, and the person challenged is unable to serve; 2) I’jaz Al-Quran from a linguistic aspect can be seen from the arrangement of words and sentences in the Al-Quran, including its tone and style, brevity and conciseness, editorial balance, and the presence of palindromes. Therefore, 3) Al Quran has an impact on those who read it by satisfying experts, thinkers, philosophers and lay people. Apart from that, the Al-Quran also satisfies the mind and soul, namely by means of conveying the Al-Quran which is varied, not monotonous, and in accordance with human nature.